2002
DOI: 10.1073/pnas.182276099
|View full text |Cite
|
Sign up to set email alerts
|

Huntington's disease age-of-onset linked to polyglutamine aggregation nucleation

Abstract: In Huntington's Disease and related expanded CAG repeat diseases, a polyglutamine [poly(Gln)] sequence containing 36 repeats in the corresponding disease protein is benign, whereas a sequence with only 2-3 additional glutamines is associated with disease risk. Above this threshold range, longer repeat lengths are associated with earlier ages-of-onset. To investigate the biophysical basis of these effects, we studied the in vitro aggregation kinetics of a series of poly(Gln) peptides. We find that poly(Gln) pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

52
719
5

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 498 publications
(787 citation statements)
references
References 32 publications
52
719
5
Order By: Relevance
“…Experiments have also shown that the tendency to form intermolecular aggregates increases with polyglutamine length. Wetzel and coworkers have carried out a series of experiments based on a variety of spectroscopic and other probes to quantify the overall rate of aggregation as a function of chain length and concentration [45,54,[65][66][67]. Their conclusions are consistent, at least qualitatively, with the expectations from polymer theory as discussed above and demonstrated in Figure 3.…”
Section: Applicability Of Polymer Physics Concepts To Study Of Aggregsupporting
confidence: 57%
See 3 more Smart Citations
“…Experiments have also shown that the tendency to form intermolecular aggregates increases with polyglutamine length. Wetzel and coworkers have carried out a series of experiments based on a variety of spectroscopic and other probes to quantify the overall rate of aggregation as a function of chain length and concentration [45,54,[65][66][67]. Their conclusions are consistent, at least qualitatively, with the expectations from polymer theory as discussed above and demonstrated in Figure 3.…”
Section: Applicability Of Polymer Physics Concepts To Study Of Aggregsupporting
confidence: 57%
“…The second prediction of Raos and Allegra appears to be at odds with findings in the amyloid literature, which suggest that the mechanism of aggregation proceeds through the formation of a structured nucleus, which presents a single, well-defined barrier [45]. It is noteworthy that Krishnan and Lindquist [93] have challenged this view in their recent work on the aggregation of a yeast prion.…”
Section: Implications Of Theoretical Predictions For Kinetics Of Aggrmentioning
confidence: 90%
See 2 more Smart Citations
“…The aggregation of both proteins is consistent with a nucleated-polymerization model, 26 and kinetic analysis revealed a monomeric nucleus in both cases, suggesting that a folding or unfolding reaction within a monomer was the thermodynamically unfavorable event prerequisite for aggregation. A monomeric nucleus was previously implicated in in-vitro aggregation of polyglutamine peptides, 27 making it difficult to distinguish which part of the tetra-Cys CRABP Htt53 chimera (either tetra-Cys CRABP or Htt domain) is mechanistically dominant in aggregation. Intriguingly, the diffraction pattern of isolated P39A tetra-Cys CRABP aggregates formed in vivo resembles the characteristic fingerprint pattern of ordered amyloid structures, suggesting a common microstructure for all types of aggregates.…”
Section: Review Of Our In Vivo Folding and Aggregation Studiesmentioning
confidence: 99%